Metode Pembuatan Sorgum Sosoh Rendah Tanin pada Pembuatan Nasi Sorgum (Sorghum Bicolor L) Instan - Wiwit Amrinola; Sri Widowati; Purwiyatno Hariyadi (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Sorghum is one of the non-rice commodities which have a relatively high content of nutrients, especially protein and carbohydrate. However, the nutritional value is to be down and relatively low due to the relatively high tannin content as an anti-nutrient. Fairly high tannin content in sorghum is also causing sorghumhas unpleasant taste and slightly bitter or "Sepet". Therefore, it is necessary to reduce the content of tannins in sorghum that is expected to improve the quality of nutrition, especially the increase in protein and starch digestibility and palatability or the flavor of sorghum products. The purpose of this study is to obtain the best method to lower tannin content in the manufacture of low-tannin sorghum milling, which will be used in the manufacture of instant rice sorghum. This research was done in two stages, namely 1) the timing of the millingstage and 2) the development stage of a method of making low-tannin sorghum milling by comparing the content of tannin reduction method with the immersion process in alkaline solution (NaOH 0.3% and 0.3% Na2CO3) and distilled water with the method of reducing tannin content without immersion process. The results of this study indicate that the best milling time that can produce milled sorghum with good physical sorghum is five minutes and the best immersion treatment that can lower the optimum tannin content is by immersing in 0.3%Na2CO3 solution for 24 hours. This method can reduce up to 77.46% tannin content.